Dynamic-Based Cluster Routing Algorithm for Data Transmission in WSN - Daljeet Kaur,; Dr Khushboo Bansal, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Wireless Sensor Network has been used for collection of information from the non-approachable areas.WSN use sensor nodes for sensing the information from the environment. Sensor nodes have been powered using energy source that is battery connection. Battery source of WSN nodes can’t be charged from any external device so that energy efficient utilization of the nodes for sensing and transmitting information is the major concern. Various approaches had been introduced in the past researches that provide better energy efficient protocol for enhancement of network lifetime and data transmission. In this paper various approaches have been implemented for WSN. Clustering based approaches have been utilized and assumed to be efficient approaches for data collection and data transmission over the network. In this paper we have reviewed DEEC, LEACH, EIP-LEACH and comparison has been done with proposed approach based on various parameter i.e Network lifetime. Experimental results of above defined approaches have been demonstrated.
Keywords: WSN; Clustering; LEACH; Cluster Head; Energy Consumption